2013
DOI: 10.1017/s1352465813000441
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant and Group Psychosocial Treatment for Depression: A Rater Blind Exploratory RCT from a Low Income Country

Abstract: Psychosocial intervention was as effective as antidepressants in reducing depression and in improving quality of life and disability at the end of therapy. However, these findings need further exploration through a larger trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Two additional studies were found through reference lists and during data extraction, which resulted in 34 randomised controlled trials included in meta-analysis (Fig. 1) (Teasdale et al ., 1984; Ross and Scott, 1985; Scott and Freeman, 1992; Scott et al ., 1997; Ward et al ., 2000; Watson et al ., 2003; Willemse et al ., 2004; Dalgard, 2006; Smit et al ., 2006; González González et al ., 2007; Spek et al ., 2007; Laidlaw et al ., 2008; Lovell et al ., 2008; Wiles et al ., 2008; Kessler et al ., 2009; Serfaty et al ., 2009; Hegerl et al ., 2010; Naylor et al ., 2010; Cramer et al ., 2011; Dwight-Johnson et al ., 2011; Ekers et al ., 2011; Joling et al ., 2011; Levin et al ., 2011; Casañas et al ., 2012; Power and Freeman, 2012; Sørensen Høifødt et al ., 2013; Wiles et al ., 2013; Williams et al ., 2013; Husain et al ., 2014; Kivi et al ., 2014; Gilbody et al ., 2015; Kanter et al ., 2015; Chowdhary et al ., 2016; Gilbody et al ., 2017).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two additional studies were found through reference lists and during data extraction, which resulted in 34 randomised controlled trials included in meta-analysis (Fig. 1) (Teasdale et al ., 1984; Ross and Scott, 1985; Scott and Freeman, 1992; Scott et al ., 1997; Ward et al ., 2000; Watson et al ., 2003; Willemse et al ., 2004; Dalgard, 2006; Smit et al ., 2006; González González et al ., 2007; Spek et al ., 2007; Laidlaw et al ., 2008; Lovell et al ., 2008; Wiles et al ., 2008; Kessler et al ., 2009; Serfaty et al ., 2009; Hegerl et al ., 2010; Naylor et al ., 2010; Cramer et al ., 2011; Dwight-Johnson et al ., 2011; Ekers et al ., 2011; Joling et al ., 2011; Levin et al ., 2011; Casañas et al ., 2012; Power and Freeman, 2012; Sørensen Høifødt et al ., 2013; Wiles et al ., 2013; Williams et al ., 2013; Husain et al ., 2014; Kivi et al ., 2014; Gilbody et al ., 2015; Kanter et al ., 2015; Chowdhary et al ., 2016; Gilbody et al ., 2017).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…While random sequence generation and allocation concealment were adequate in the majority of cases, the most common reason for risk of bias was incomplete outcome data. Three studies were given a low risk of bias rating on all applicable criteria (Wiles et al ., 2013; Husain et al ., 2014; Gilbody et al ., 2017). Two additional studies (Smit et al ., 2006; Joling et al ., 2011) fell just short of this mark because no pre-registered study protocol could be found (selective reporting unclear).…”
Section: Resultsmentioning
confidence: 99%
“…In Iran, Malakouti et al 39 sought to reduce the number of suicides. In Pakistan, Husain et al 40 compared the effectiveness of psychotherapy to antidepressant medications in reducing depression and improving quality of life. This group compared two integrated interventions without contrasting it to usual care and found no difference between these two arms.…”
Section: Resultsmentioning
confidence: 99%
“…All scales have been validated for use in the Urdu language and have been used in previous studies in Pakistan 33. Adverse effects will be monitored using scales that have been specifically designed for minocycline and celecoxib.…”
Section: Methodsmentioning
confidence: 99%